Effect of low-temperature ethylene oxide and electron beam sterilization on the in vitro and in vivo function of reconstituted extracellular matrix-derived scaffolds. (October 2015) - Proffen, Benedikt L; Perrone, Gabriel S; Fleming, Braden C; Sieker, Jakob T; Kramer, Joshua; Hawes, Michael L; Murray, Martha M
Reconstituted extracellular matrix (ECM)-derived scaffolds are commonly utilized in preclinical tissue engineering studies as delivery vehicles for cells and growth factors. Translation into clinical use requires identifying a sterilization method that effectively removes bacteria but does not harm scaffold function. To determine effectiveness of sterilization and impact on ECM scaffold integrity and function, low-temperature ethylene oxide and 15 kGy electron beam irradiation techniques were evaluated. Scaffold sterility was assessed in accordance to United States Pharmacopeia Chapter 71. Scaffold matrix degradation was determined in vitro using enzymatic resistance tests and gel electrophoresis. Scaffold mechanics including elastic modulus, yield stress and collapse modulus were tested. Lastly, 14 Yorkshire pigs underwent ACL transection and bio-enhanced ACL repair using sterilized scaffolds. Histologic response of ligament, synovium, and lymph nodes was compared at 4, 6, and 8 weeks. Ethylene oxide as well as electron beam irradiation yielded sterile scaffolds. Scaffold resistance to enzymatic digestion and protein integrity slightly decreased after electron beam irradiation while ethylene oxide altered scaffold matrix. Scaffold elastic modulus and yield stress were increased after electron beam treatment, while collapse modulus was increased after ethylene oxide treatment. No significant changes in ACL dimensions, in vivo scaffold resorption rate, or histologic response of synovium, ligament, and lymph nodes with either terminal sterilization technique were detectable. In conclusion, this study identifies two methods to terminally sterilize an ECM scaffold. In vitro scaffold properties were slightly changed without significantly influencing the biologic responses of the surrounding tissues in vivo. This is a critical step toward translating new tissue engineering strategies to clinical trials.